Sources of gray mold rot resistance in strawberries in the environments of the Middle Urals - E. Yu. Nevostrueva (Труды по прикладной ботанике, генетике и селекции)
Background. One of the most common diseases affecting garden strawberry fruits is gray mold rot. It is capable of destroying more than half of the fruit harvest in the wet seasons observed in the Middle Urals in recent years. Largesized marketable berries are the first to be affected. The disease does not entail the plant’s death, which is one of the probable reasons why this problem has not been studied much. Strawberry cultivars yielding firmer fruit are known to be less susceptible to gray mold damage, so they can be used as source material in breeding practice. There are few such accessions in the strawberry collection maintained at Sverdlovsk Horticultural Breeding Station, and those available, being of foreign origin, demonstrate poor winter hardiness, thus precluding their use in crosses as female parents. An assessment of the damage inflicted by gray mold rot on strawberry fruit may help to identify promising source material where gray mold resistance would be combined with a set of other commercially attractive traits.Materials and methods. The evaluated material comprised 19 selected seedlings produced from crosses between source accessions that yielded berries of different firmness. Cv. ‘Festivalnaya’ served as the reference. The study was based on conventional techniques.Results and conclusions. As a result of the evaluation for gray mold resistance, seedling 2-45-10 (Solovushka × Dukat) was identified as a promising female parent. When compared with the reference, this seedling manifested winter hardiness, high yield, and large size of berries. Seedlings 2-54-11 (Amulet × Marmolada) and 3-45-10 (Solovushka × Dukat), with the response to freezing scored 2.0, may be involved in crosses as male parents.